Gayle Rogers. Modernism and the New Spain. Oxford/New York: Oxford UP, 2012. xvi + 283 pp. - Juan Francisco Maura (Studies in 20th & 21st Century Literature, 2015)
Review of Gayle Rogers. Modernism and the New Spain. Oxford/New York: Oxford UP, 2012. xvi + 283 pp.
Keywords: Gayle Rogers; Modernism; Spain